Integration of Social Media Technologies with ERP:A Prototype Implementation - SHANKARARAMAN, Venky (Institutional Knowledge at Singapore Management University, 2013)
Many organizations use social media to enhance collaboration both internally among employees and externally with customers and partners. However, it is not sufficient to just create a presence in some key social environments such as Facebook or YouTube. In order to fully leverage the value of social media, organizations must integrate social media with their business processes, which means new solutions have to be developed that extend existing enterprise systems. In this paper, we present a prototype solution that demonstrates the integration of social media with the order processing process. The implemented solution brings together the embedded best practice processes within an ERP with unstructured data from the social media.